A Child with Tethered Cord Syndrome - Safarini, Bekti (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Tethered Cord Syndome (TCS) refers to a group of neurological disorders related to malformations of the spinal cord, pulling of the spinal cord at the base of spinal canal. Tethered cord syndrome can be seen at any age but most often during childhood. A few children complain of diffuse pain in lower extremitiesor urological symptoms, 20% - 30 % of the patients will have a neurogenic bladder. A 9 years old girl, complained to have a flank pain and eneuresis. A mass is palpable at right flank. Ultrasound revealed duplex hydronephrosis and hydroureter with trabeculated bladder. Voiding Cystouretrography showed grade V vesicoureteral reflux (VUR) and neurogenic bladder appearance. Lumbosacral MRI demonstrated tethered cord with adjacent lipoma and spina bifida (Sains Medika, 4(1):89-96).